Pharmacometric analyses of alectinib to facilitate approval of the optimal dose for the first‐line treatment of anaplastic lymphoma kinase–positive non‐small cell lung cancer. (21st September 2021) - Hsu, Joy C.; Jaminion, Felix; Guerini, Elena; Balas, Bogdana; Bordogna, Walter; Morcos, Peter N.; Frey, Nicolas
Abstract: Alectinib is an anaplastic lymphoma kinase (ALK) inhibitor approved for treatment of ALK ‐positive non‐small cell lung cancer. Population pharmacokinetic (PK) models were developed for alectinib and its major active metabolite M4 using phase I/II PK data in crizotinib‐failed patients ( N = 138). The PK profiles were best described by two separate models with similar structure for both entities: open one‐compartment models with sequential zero/first‐order input and first‐order elimination rate. Body weight with fixed allometric scaling factor on clearance and volume of both entities was the only significant covariate. Bayesian feedback analyses of the PK data collected from Japanese and global treatment‐naïve patients in phase III studies ( N = 334) confirmed the body weight effect. Landmark Cox proportional hazards analyses of progression‐free survival in treatment‐naïve patients identified the average molar concentrations of both entities alectinib and M4 during the first 6 weeks of treatment as a significant covariate, with an optimal response achieved for concentrations above 1040 nmol/L. With 600 mg twice daily (b.i.d.), 92% of global patients are above this threshold concentration, compared with only 43% of patients with 300 mg b.i.d. In Japan, where the body weight distribution is lower, the approved 300 mg b.i.d. dose brings about 70% of Japanese patients above this threshold. Logistic regression analyses found no significant relationship between the combined alectinib–M4 molar concentration and first occurrence of adverse events. These pharmacometric results were used to expedite and facilitate regulatory approvals of 600 mg b.i.d. for first‐line ALK ‐positive NSCLC in the United States and European Union in 2017 and in China in 2018.